Enhancing Waqf management through fintech in Malaysia: a conceptual framework on the Technology Acceptance Model (TAM) / Habeebullah Zakariyah ... [et al.] - Zakariyah, Habeebullah; Salaudeen, Adnan Opeyemi; Othman, Anwar Hasan Abdullah; Rosman, Romzie (Universiti Teknologi MARA Selangor, 2022)
In Malaysia, academic studies on the mobilisation of cash waqf and enhancing its role as a mechanism for socio-economic development through the adoption of fintech (financial technology) is highly abound. Additionally, there are calls from stakeholders to adopt best practices fintech solutions in waqf practice to drive efficiency in waqf transactions management, ranging from fund mobilisation, investment and disbursement and connecting donors to fundraisers. This study aims to fill a knowledge gap by explaining the factors regarding the deployment of fintech related to the 4th Industrial Revolution to improve the collection and investment of cash waqf. This paper proposes a conceptual framework for expanding cash waqf collection and performance through fintech in response to the fourth industrial revolution wave study predicting computer technology adoption behaviour. The proposed model is based on a modified framework of Davis's technology acceptance model (TAM) method, which Wallace and Sheetz (2014) adopted in their study titled 'The Adoption of Software Measures: A Technology Acceptance Model (TAM) Perspective'. The model seeks to propose measurement for the independent variable of fintech awareness and knowledge, ease and usefulness of fintech, attitude towards fintech and finally, trust and confidence toward the adoption of fintech. Finally, this study will serve as a valuable guide and provide future research insights to explore this avenue further.